The Bicha Louca (Crazy Fag) Character and the Construction of a Network of Actorial Work in Brazil during the Civil-Military Dictatorship (1964-1985) - Ferreira da Rocha Junior, Alberto (Revista Brasileira de Estudos da Presença, 2021)
The article proposes the existence of an actorial network that created a character-type of the male homosexual, which could be called the bicha louca (crazy fag). Actors such as Nestor Montemar, Raul Cortez, Ítalo Rossi and Emiliano Queiroz participated in this network, contributing to the theatre being a space of visibility for the LGBT population and of resistance to the moral and political repression in the period of the Brazilian civil military dictatorship (1964-1985).